Bimbingan Kelompok Pranikah Dalam Mencegah Perceraian Pada Calon Pengantin - Rita Anriani; Nurjanah Nurjanah (Al-Ittizaan: Jurnal Bimbingan Konseling Islam, 2021)
The increasing number of divorce cases in society lately has caused concern for prospective brides, considering that the family is one of the best places for each individual to build life. Every divorced couple will have a negative impact on the economy, social and culture of the couple, especially for those couples who have children. Children are one of the victims of divorced couples. Therefore, it is necessary to provide briefing and procedures for dealing with domestic life for the bride and groom, namely the marriage guidance program for the prospective bride and groom to prepare the couple to face the household. The purpose of this study is how to guide premarital groups in preventing divorce for prospective brides at the KUA Kecematan Dumai Timur. This study uses a qualitative descriptive, the subject in this study is the prospective bride. As for the results of this study, premarital group guidance is very effective in preparing prospective brides to face the household. The stages used in pre-marital guidance at the East Dumai District KUA are: the formation stage, the transition stage, the activity stage, and the termination stage.